Humanity and Social Ethics in Building Community Solidarity during Democratic Transitions - Fauzan, Ahmad; Santoso, Budi; Ramadhan, Rizal (Journal Social Humanity Perspective, 2025)
This paper explores the place of humanity and social ethics in the process of constructing community solidarity during a democratic transition, and how the ethical values become management resources in an institutionally volatile context. The study, in a qualitative mode, investigates the theory of humanity-based values in the basis of morality of trust, how social ethics can transform topical conflicts by creating positive results, and how moral obligations can help maintain the community. Data were obtained based on the in-depth interviews with community leaders, activists, and the members of transitional organizations permitting to get profound insights into the practices of solidarity in real life. The results indicate that humanity and ethics are not fringe and symbolic, but core processes of dealing with uncertainty, building resiliency, and strengthening legitimacy within transitional governance. This adds to management scholarship in that it reformulates ethics as strategic assets to the stability of organizations and society instead of compliance and normative ideals. Practically, the study underlines that managers and policymakers should foster ethical leadership, integrate participatory strategies and make responsibility, honesty and care norms of the organization. These commitments help communities to overcome conflict, build trust and develop collective identity despite political disruption. The study adds to the discussion of the study of management and governance by showing that solidarity in the issue of democratic transitions is not a spontaneous phenomenon, but rather one that is controlled by deliberate ethical practices, thus, highlighting the fact that ethics, humanity, and sustainable development of democracy cannot be divided.